Logos in nesmrtnost - Petar Šegedin (Phainomena, 2020)
The article represents a detailed analysis of the proof of immortality of the soul in the dialogue Phaedo, whereat the author dedicates specific attention to the question of the causation of the idea as that, which is by itself. Upon the basis of the demonstrated ontological-causational foundation of ontic characteristics and relations in the realm of the ideal, the paper follows Plato’s discussion not only of an external, merely formal connection, but of an essentially internal interrelatedness and even kinship between the soul and the idea. The reach of the proof of soul’s immortality can, thus, be recapitulated in the thesis that the intellectual causation of what is by itself develops, demonstrates, and establishes itself, according to its own essence, as the inextinguishable origination of life, which is at work not only in each singular living being, but also in all of them together.